2007
DOI: 10.1007/s10493-007-9069-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-omnia moriantur—toxicity of mancozeb on dead wood microarthropod fauna

Abstract: The effect of Dithane M-45 (dithiocarbamate fungicide; active substance: mancozeb) was studied on microarthropod fauna inhabiting dead wood. Although the exposure was almost never 100% lethal for the majority of observed taxa, almost all (Mesostigmata, Oribatida, some Uropodina, Actinedida, Collembola and Diplopoda) showed very high correlation between concentration of the fungicide and mortality (r > 0.86). Only Stigmaeidae showed low correlation (r = 0.293). For the majority of taxa LC(50 )values were close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
6
1
Order By: Relevance
“…Previously, we reported that the majority of taxa of microarthropods found in wood dust show some tolerance to short-term exposure to mancozeb (AdAmski et al 2007). Data presented in the present paper can lead to the conclusion that a single pesticide spraying does not necessarily lead to massive mortality of invertebrates.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Previously, we reported that the majority of taxa of microarthropods found in wood dust show some tolerance to short-term exposure to mancozeb (AdAmski et al 2007). Data presented in the present paper can lead to the conclusion that a single pesticide spraying does not necessarily lead to massive mortality of invertebrates.…”
Section: Discussionsupporting
confidence: 64%
“…Similar results were also observed ) on control and pesticideexposed plots. Data are means ± SD by other authors, who reported the susceptibility of springtails to several pesticides (Joy et al 2005(Joy et al , vig et al 2006, and by our group, where more than 50% of these arthropods would theoretically die if the fungicide was sprayed over their habitats (AdAmski et al 2007). In the present study we did not observe any significant decrease in the abundance of springtails during short-term and long-term exposure (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations